Genetic polymorphisms in oxidative stress‐related genes are associated with outcomes following treatment for aggressive B‐cell non‐Hodgkin lymphoma. Issue 6 (12th April 2014) - Gustafson, Heather L.; Yao, Song; Goldman, Bryan H.; Lee, Kristy; Spier, Catherine M.; LeBlanc, Michael L.; Rimsza, Lisa M.; Cerhan, James R.; Habermann, Thomas M.; Link, Brian K.; Maurer, Matthew J.; Slager, Susan L.; et al.
<x xml:space="preserve">Abstract</x> Variable survival outcomes are seen following treatment for aggressive non‐Hodgkin lymphoma (NHL). This study examined whether outcomes for aggressive B‐cell NHL are associated with single nucleotide polymorphisms (SNPs) in oxidative stress‐related genes, which can alter drug metabolism and immune responses. Genotypes for 53 SNPs in 29 genes were determined for 337 patients given anthracycline‐based therapies. Their associations with progression‐free survival (PFS) and overall survival (OS) were estimated by Cox proportional hazard regression; associations with hematologic toxicity were estimated by logistic regression. To validate the findings, the top three SNPs were tested in an independent cohort of 572 DLBCL patients. The top SNPs associated with PFS in the discovery cohort were the rare homozygotes for MPO rs2243828 (hazard ratio [HR] = 1.87, 95% confidence interval [CI] = 1.14–3.06, P = 0.013), AKR1C3 rs10508293 (HR = 2.09, 95% CI = 1.28–3.41, P = 0.0032) and NCF4 rs1883112 (HR = 0.66, 95% CI = 0.43–1.02, P = 0.06). The association of the NCF4 SNP with PFS was replicated in the validation dataset (HR = 0.66, 95% CI = 0.44–1.01, P = 0.05) and the meta‐analysis was significant (HR = 0.66, 95% CI = 0.49–0.89, P < 0.01). The association of the MPO SNP was attenuated in the validation dataset, while the meta‐analysis remained significant (HR = 1.64, 95% CI = 1.12–2.41). These two SNPs showed similar trends with OS in the meta‐analysis (for NCF4, HR = 0.72, 95% CI = 0.51–1.02, P = 0.07 and for MPO, HR = 2.06, 95% CI = 1.36–3.12, P < 0.01). In addition, patients with the rare homozygote of the NCF4 SNP had an increased risk of hematologic toxicity. We concluded that genetic variations in NCF4 may contribute to treatment outcomes for patients with aggressive NHL. Am. J. Hematol. 89:639–645, 2014. © 2014 Wiley Periodicals, Inc.